Discovering the languages of peace: Handbook of Sociopsychodrama (Morepress Books, 2023)
The idea of the book is a result of cooperation between the authors who have also been trainers on the curriculum both on zoom webinars and in the spring school – Børge Kristoffersen, Mariolina Werner Guarino, Margarida Belchior, Monica Westberg and Jana Damjanov. Two more trainers who have been on webinars Monica Zuretti and Fernan Rodriguez Cetran have been a great inspiration for the whole project. The term sociopsychodrama itself comes from our friend Monica Zuretti who is from Argentina and who has been developing sociopsychodrama practice all over the world. With her friend Monica Westberg they have worked and started spreading sociopsychodrama over Europe since 1980s. The rest of us who wrote the chapters in this handbook are their students and friends and colleagues and we are deeply grateful for all we have learnt. The seed for this project and this book was planted in 2018, in Berlin, where we had international meeting and we are grateful to all the colleagues who were there with us and helped us to plant these seeds. This is not usual book, it is a combination of very practical texts, with explanation of theory, what sociopsychodrama is, and examples and suggestions of exercises and warm ups that you as a reader can easily use. But, it is up to you reader to adapt these also to your work setting. On the other hand, it is also combined with the chapters, which are new readings of Moreno’s theory, development of that theory and philosophy, reflections on personal stories and examples from professional work. This book will help readers to start their own journey in sociopsychodrama, and we are all very happy that we have been able to do it! Enjoy it and take out the best for you from it!